The impact of coercive and assertive communication styles on children’s perception of chores: an experimental investigation - Marici, Marius; Runcan, Remus; Cheia, Gheorghe; David, Gheorghe (Frontiers in Psychology, 2024)
Introduction This article presents the findings of an experimental study aimed at investigating the impact of coercive and assertive communication on children’s emotional responses and behavioral tendencies within parent–child interactions. Methods The study tested four hypotheses related to children’s feelings, personalization bias, the need to express their point of view, and the desire to retreat to their room alone. Short audio stimuli recorded by a female assistant, representing a mother addressing her child, were utilized to create five different communication situations. The experimental procedure involved participants listening to the audio stimuli and answering related questions. The study included 123 participants between the ages of 9 and 13, with an equal gender distribution. Results The results of One-Way ANOVA tests indicated significant differences among the four types of communication in terms of unpleasant feelings, personalization bias, listening to a personal point of view, and retreating into a personal room. The findings suggest that coercive communication elicited more negative emotional responses and stronger tendencies toward personalization bias, expressing personal opinions, and seeking solitude compared to assertive communication. Discussion The implications of these findings highlight the importance of promoting positive and respectful communication strategies in parent–child relationships to foster children’s emotional well-being and healthy behavioral development.